Rewolucja 1956 w literaturze węgierskiej. Na marginesie literackiego kanonu - Piotrowiak-Junkiert, Kinga (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article is an attempt at an outline of the situation in Hungarian literature confronted with the revolution of 1956. The events of the Hungarian October are some of the more frequent themes in revisionist literature. Selected examples of literary works show the most important features of that literature, writing strategies, patterns of artistic message. From the wide selection of the literature, a poem, fragments of a diary, a novel, and an authobiographical essay by Sandor Marai, Gyorgy Moldova, Istvan Orkeny and Imre Kertesz were selected.